Role of Fluorescent Staining and Ziehl-Neelsen Techniques in The Detection of Mycobacterium Tubercle Bacilli in Lymph Node Aspirate - Raina, Varsha; Gupta, Kamna; Thakral, Rajender Kumar; Mohan, Alok; Kunika,; Kaur, Harmanpreet; Tandon, Kanav (Journal of College of Medical Sciences-Nepal, 2024)
Background Tuberculosis is the important disease of infectious etiology especially in the developing nations. It is a major health issue in India. FNAC is an economic and rapid tool having high diagnostic accuracy for LN tuberculosis. Present study was conducted to describe the role of fluorescent staining and Ziehl- Neelsen techniques in detecting Mycobacterium tubercle bacilli on FNAC samples of tubercular lymphadenitis. Methods This prospective study was carried out at Department of Pathology, Muzaffarnagar Medical College, U.P. It included 100 patients having enlarged lymph nodes which were suspected of TB. After FNAC, cytological examination was done and smears prepared were stained with ZN stain and Auramine Rhodamine (AR) stain. Results Twenty eight (28.0%) cases were found in 21-30 years age group followed by 20 cases (20%) in 31- 40 year age group and 11-20 year age group. Most were females forming female to male ratio 1.7:1. Cytomorphologically, four patterns were observed– Necrotizing granulomatous lymphadenitis in 41% cases, Granulomatous lymphadenitis in 29% cases, only Necrotizing lymphadenitis in 19% cases and Necrotizing lymphadenitis with suppuration in 11% cases. ZN staining showed AFB in 35% cases while AFB was not seen in 65% cases. Out of these 65% cases, fluorescent staining was positive in 29%, indicating significant association of fluorescent staining with ZN method. Conclusions Only with the cytological findings of lymph node, it is difficult to arrive at confirmatory diagnosis of TB. Fluorescence Microscopy (FM) increases the sensitivity for diagnosing TB in underdeveloped nations with high tuberculosis prevalence, such as India.